Antibacterial Activity of Chrysanthemum indicum, Centella asiatica and Andrographis paniculata on Bacillus cereus and Listeria monocytogenes under Low pH Stress - Utami, Christina Vania; Pitinidhipat, Nateepat; Yasurin*, Patchanee (CURRENT APPLIED SCIENCE AND TECHNOLOGY, 2018)
Classic food preservation methods do not guarantee to inhibit Bacillus cereus and Listeria monocytogenes growth. The application of natural antibacterial agent is an alternative way to control their growth. Asia herbs, Chrysanthemum indicum, Centella asiatica, and Andrographis paniculata were used in this experiment to test their antibacterial activity under low pH stress. Their antibacterial activities of 95% ethanolic crude extracts were tested on B. cereus and L. monocytogenes 10403S under different low pH stress by agar disc diffusion method. The best antibacterial effect on both bacteria was found at low pH stress condition. Lowering pH also acts as one inhibitory effect. The result of in vitro antibacterial effect as inhibition zone at pH 7.0, 6.5,6.0, 5.5, showed that the inhibition zone diameters of C. indicum extracts were 7.62±1.18.7.87±2.35, 6.25±3.06 and 9.50±2.14 cm, while the inhibition zone diameters of C. asiatica extracts were 8.75±1.03, 8.75±2.66, 7.75±2.37 and 9.12±1.96 cm and A. paniculata extracts were 9.75±1.75, 5.87±3.52, 8.5±1.23 and 9.33±1.63 against L. monocytogenes 10403S, respectively. Under the same condition, the inhibition zone diameters of C. indicum extracts at 2.12±0.64,1.37±0.92, 0.93±0.78 and 6.00±3.25 cm, the inhibition zone diameters of C. asiatica extracts at 0.62±0.44, 2.25±0.46, 1.75±0.28 and 6.50±1.60 cm and A. paniculata extracts at 0.87±0.79,1.25±0.60, 2.00±1.65 and 6.00±1.31, respectively against B. cereus. All 95% ethanolic crude extracts showed more inhibition effect on L. monocytogenes 10403S than B.cereus. However, the promising active antibacterial compounds in all three herbs are needed to be identified. The MBCs of A. paniculata, C. asiatica and C. indicum showed 4, 16 and >32 μl/ml against B. cereus while A. paniculata and C. asiatica showed 16 and >32 μl/ml against L. monocytogenes 10403S. Keywords: Antibacterial, Chrysanthemum indicum, Centella asiatica, Andrographis paniculata, Bacillus cereus, Listeria monocytogenes 10403S, Low pH stress, Herb E-mail: patchaneeysr@au.edu